2004
DOI: 10.1002/syn.20020
|View full text |Cite
|
Sign up to set email alerts
|

Brain vesicular acetylcholine transporter in human users of drugs of abuse

Abstract: Limited animal data suggest that the dopaminergic neurotoxin methamphetamine is not toxic to brain (striatal) cholinergic neurons. However, we previously reported that activity of choline acetyltransferase (ChAT), the cholinergic marker synthetic enzyme, can be very low in brain of some human high-dose methamphetamine users. We measured, by quantitative immunoblotting, concentrations of a second cholinergic marker, the vesicular acetylcholine transporter (VAChT), considered to be a "stable" marker of cholinerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…These results suggest that the inactivation of nicotinic acetylcholinergic transmission is an essential factor for the appearance of MAP-seeking behavior, and, thus, the normalization of the inactivated state may result in the suppression of the reinstatement. In a clinical study, it has been demonstrated that the down-regulation of choline acetyltransferase and elevation of the expression of the vesicular acetylcholine (ACh) transporter develop in a MAP user's brain (2). This result suggests that elevation of the expression of the vesicular ACh transporter may be due to compensation for the down-regulation of choline acetyltransferase and that these changes may lead to the inactivated state of nicotinic acetylcholinergic transmission.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…These results suggest that the inactivation of nicotinic acetylcholinergic transmission is an essential factor for the appearance of MAP-seeking behavior, and, thus, the normalization of the inactivated state may result in the suppression of the reinstatement. In a clinical study, it has been demonstrated that the down-regulation of choline acetyltransferase and elevation of the expression of the vesicular acetylcholine (ACh) transporter develop in a MAP user's brain (2). This result suggests that elevation of the expression of the vesicular ACh transporter may be due to compensation for the down-regulation of choline acetyltransferase and that these changes may lead to the inactivated state of nicotinic acetylcholinergic transmission.…”
Section: Discussionmentioning
confidence: 86%
“…1b). Scopolamine, a muscarinic antagonist, did not block the nicotineinduced attenuation of cue-induced and MAP-primed reinstatement (F [2,21] ϭ 0.9 and 0.4; P Ͼ 0.4 compared with the cued and MAP-primed nicotine-pretreated group, respectively). In addition, mecamylamine blocked the effects of donepezil on reinstatement induced by a cue and MAP priming (F[2,21] ϭ 59.9 and 114.8; P Ͻ 0.001 compared with the donepezil-pretreated group given the cue and MAP priming, respectively), whereas scopolamine did not antagonize the effect of donepezil on reinstatement induced by a cue and MAP priming (F[2,21] ϭ 1.3 and 0.3; P Ͼ 0.3 compared with the cued and MAP-primed donepezil-pretreated group).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary findings suggest regional-specific changes in cerebral blood flow following the infusion of physostigmine or scopolamine compared to saline (Adinoff et al, 2005). To date, the only published studies exploring neural cholinergic systems in this population have reported that ChAT and vesicular ACh transporter (VAChT) concentrations in the autopsied brains of cocaine-addicted subjects did not differ from those of heroin-addicted (VAChT, ChAT) or control subjects (VAChT) (Kish et al, 1999;Siegal et al, 2004).…”
Section: Summary and Future Directions For Clinical Researchmentioning
confidence: 92%